2019
DOI: 10.18502/keg.v1i1.4405
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Copper and Manganese on the Amorphization Process in a Thin Fe–Si–Mg–O Film

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…It presumably corresponds to two amorphous phases with slightly different chemical compositions. These results are consistent with the experimental data reported in [ 22 , 23 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…It presumably corresponds to two amorphous phases with slightly different chemical compositions. These results are consistent with the experimental data reported in [ 22 , 23 ].…”
Section: Resultssupporting
confidence: 94%
“…The studies [ 22 , 23 ] demonstrated that a thermally stable amorphous phase is formed in the glass film surface after a full cycle of HTA in the temperature range of α → γ transformation. Based on the thermodynamic calculations, an assumption has been made about chemical interactions leading to the formation of an amorphous phase and its estimated chemical composition has been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…This result is confirmed by high-resolution transmission electron microscopy (HRTEM) images of the cross-sections of as-prepared CoN and CoMnN films, as demonstrated in Figure b,c, respectively. The areas marked with red squares were chosen for fast Fourier transform (FFT) analyses, as shown in the insets, in which clear diffraction spots can be found for CoN films [points inside yellow cycles, corresponding to an interplanar distance d = 2.13 Å, consistent with a cubic CoN (200) orientation], whereas no spot is observed for CoMnN films, in agreement with XRD results and evidencing the role of Mn as a “amorphizing” agent . To further understand the compositional distribution of CoMnN films, HAADF-STEM and EELS were performed on as-deposited CoMnN films, with corresponding mappings shown in Figure d.…”
Section: Resultssupporting
confidence: 52%
“…In metallic alloys, efforts have been made to substitute Co, Ni, or Fe by Mn as an effective means to alter their magnetic and electrical behavior. In magneto-ionics, Mn introduction may also give specific advantages. First, Mn, as an “amorphizing” agent, could favor the formation of an amorphous phase, which would promote planar-like diffusion fronts for ion motion (because, otherwise, ion motion preferentially occurs along grain boundaries). Also, Mn-substitution could introduce more defects in the crystal lattice and increase electrical resistivity, possibly leading to the modification of electrical properties, from metallic-like to semi-metallic or semiconducting behavior .…”
Section: Introductionmentioning
confidence: 99%
“…Phase and structure composition for alloy Fe-3%Si-0.5%Cu [11][12][13] surface with MgO as thermostable coating, was investigated during ceramic-metallic film formation when hightemperature annealing and interesting effect of Fe-based amorphous phase formation was detected in the material surface layer…”
Section: Introductionmentioning
confidence: 99%